Factors affecting the performance of small and medium enterprises regarding the sustainable development goals: The case of foreign direct investment firms in Vietnam - Nguyen Thi Phuong Thu; Vu Ngoc Xuan (Economies, 2023)
The owners of SMEs in Vietnam mainly focus on business performance in the short term. In recent years, FDI firms have demonstrated interest in both business efficiency and sustainable development. These issues have attracted the attention of scientists and policy makers in Vietnam. Therefore, this study aimed to determine the factors affecting the performance of small and medium enterprises in Vietnam regarding the Sustainable Development Goals (SDGs). Using the latest published survey data up to March 2022 for food and beverage, wood and steel foreign direct investment enterprises, combined with a data envelope analysis model in step one and Tobit regression in step two, the results from this quantitative study are as follows: (1) the production efficiency index of Vietnamese FDI enterprises ranges from 82.5% to 89% depending on the industry (assuming variable output to scale); (2) the factors financial leverage, renewable consumption, scale and operating time are related to the performance of FDI enterprises, and have a positive effect on performance; and (3) financial leverage and renewable consumption can generally boost a firm's performance in the case of FDI SMEs in the food and beverage, wood and steel industries. This research also suggests some solutions to achieve the Sustainable Development Goads (SDGs) in the FDI SMEs of Vietnam.
Keywords: 330; financial leverage (FL); foreign direct investment (FDI); operating time (OT); renewable consumptions (RC); scale (SC); small and medium enterprises (SMEs)